Identification of catchment areas with phosphorus pollution risk for lowland river water quality - Aleksandra Steinhoff-Wrześniewska; Krzysztof Pulikowski; Maria Strzelczyk; Marek Helis (Journal of Water and Land Development, 2024)
The study aimed to analyse the seasonal variability of phosphorus concentrations and phosphorus content and the impact of catchment development of the Panew Mała River. The study presents the findings of a two-year experimental investigation (comprising 17 measurement series across 12 measurement cross-sections) into the concentration of phosphorus (P) and its soluble form, orthophosphates (PO42−). The mean phosphate concentrations were found to be low, with a range of 0.03 to 0.08 PO42− mg∙dm−3. In contrast, the total phosphorus concentrations were relatively high, with a range of 0.11 to 0.43 mg∙dm−3 The seasonal variability was analysed based on quarterly means and half-yearly periods covering quarters II and III (spring–summer) and quarters I and IV (autumn–winter), respectively. The analysis of spatial variability was conducted using cluster analysis according to Ward’s method, with the Euclidean distance employed as a measure of distance and the results related to the utilisation of different catchment area. Due to the slight differences in the phosphate concentration, the total phosphorus concentration was analysed in detail. The analysis of variance showed no significant differences between phosphorus concentrations in certain quarters, while greater variations were obtained for half-yearly periods. The applied method of grouping the sampling sites made it possible to distinguish several groups of sampling sites, which indicate relations between the values of phosphorus concentration in the waters of Mała Panew and the type of use of the catchment area.